Uji Potensial Ekstrak Etanol Alang-Alang Sebagai Pupuk Cair Pengendali Jamur Fusarium SP - Khusnul Khotimah; Dwi Kartika Risfianty; Baiq Naili Dewi Atika; Pahmi Husain; irma Risvana Dewi (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2022)
The Fusarium spcan infect plants and cause withered diseases, it is a pathogenic fungus that greatly harms and causes losses from crop failure in the pepper plnt and various other fungus plnts to infect nd cause losses and crop failure by 50 %. The diseases strikes, the plant from the seedling age to adulthood. The reed extract contains flavonoid and folifenol can be used as a fungicidaland it has the lethal properties of couse gero, which is an antimicrobial compound, which is intended to test the potential grass-ethanol extract as liquid fertilizer s fusarium sp. The research method used in this study is experimental in the laboratory to know the potential ethanol extract in suppress the growth of the fusarium sp the study, which observations from reeds, has fungal and antibacterial compounds that can impede the growth oh the fusarium sp.